Equality in Islam: Contrary Version of Prophetic Traditions and Islamic Theories in Southeast Asia - Alwy Ahmed; Muk Andhim; Hanan Zakirah Harun; Shahizanan Tajadin (Penerbit Hellow Pustaka, 2026)
societies, the interpretation of Hadith on equality has undergone significant contra version, reflecting ongoing debates between classical readings and contemporary understandings. This study aims to analyse how Prophetic traditions are employed within Islamic theories to frame equality in Muslim societies of Southeast Asia. Equality is one of the fundamental tenets of Islam, rooted in both Qur'anic guidance and Prophetic traditions that emphasise justice, brotherhood, and human dignity. The study uses a qualitative, field-based methodology that includes observations in places of worship, including madrasahs and pesantrens and interviews with Islamic scholars, educators, and community leaders. Field research is supplemented by content analysis of a few chosen Hadith and academic publications to show how notions of equality are developed and used. According to a preliminary study, the most recent developments in Islamic thinking emphasise gender justice, economic fairness, and interreligious tolerance, whereas classical interpretations place more emphasis on spiritual and community equality. This suggests that Southeast Asian Muslims are redefining equality in their particular circumstances through a continuous interaction between tradition and modernity. By providing an integrative framework that blends Hadith analysis, Islamic theory, and firsthand Southeast Asian experiences, the research advances both Islamic studies and socio-religious scholarship scientifically.